2009
DOI: 10.1002/hbm.20726
|View full text |Cite
|
Sign up to set email alerts
|

Advanced time‐series analysis of MEG data as a method to explore olfactory function in healthy controls and Parkinson's disease patients

Abstract: This is the first study to show that time-series analysis of MEG data, including spectral power and SL, can be used to detect odor-induced changes in brain activity. In addition, differences in odor-induced brain activity were found between patients with PD and controls using analysis of SL, but not of spectral power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…We subdivided the included articles into two main groups according to the brain network the analysis was focused on: motor network-focused, in which we treated the tremor network as a sub-category, and whole-brain network focused. Since a series of articles on the neurophysiological basis of neuronal entrainment in PD (Te Woerd, Oostenveld, Bloem, De Lange, & Praamstra, 2015;Te Woerd, Oostenveld, De Lange, & Praamstra, 2014;Te Woerd, Oostenveld, De Lange, & Praamstra, 2017;Te Woerd, Oostenveld, de Lange, & Praamstra, 2018), as well as four other articles (Anninos, Adamopoulos, Kotini, & Tsagas, 2016;Boesveldt, Stam, Knol, Verbunt, & Berendse, 2009;Gomez et al, 2011;Suntrup et al, 2013) tended to stand alone from the rest of this review, these will not be discussed in the results section, but the main findings are provided in Table 1. 3 | RESULTS Neurophysiological measures relevant for this review; explanation of the measures can be found in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…We subdivided the included articles into two main groups according to the brain network the analysis was focused on: motor network-focused, in which we treated the tremor network as a sub-category, and whole-brain network focused. Since a series of articles on the neurophysiological basis of neuronal entrainment in PD (Te Woerd, Oostenveld, Bloem, De Lange, & Praamstra, 2015;Te Woerd, Oostenveld, De Lange, & Praamstra, 2014;Te Woerd, Oostenveld, De Lange, & Praamstra, 2017;Te Woerd, Oostenveld, de Lange, & Praamstra, 2018), as well as four other articles (Anninos, Adamopoulos, Kotini, & Tsagas, 2016;Boesveldt, Stam, Knol, Verbunt, & Berendse, 2009;Gomez et al, 2011;Suntrup et al, 2013) tended to stand alone from the rest of this review, these will not be discussed in the results section, but the main findings are provided in Table 1. 3 | RESULTS Neurophysiological measures relevant for this review; explanation of the measures can be found in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Experimentally, several functional imaging studies, using positron emission tomography (PET) (Dade et al 1998;Zald and Pardo 2000;Savic and Gulyas 2000;Hummel et al 2009), functional magnetic resonance imaging (fMRI) (Levy et al 1999;Weismann et al 2001;Wang et al 2005), magnetoencephalography (MEG) (Tonoike et al 1998;Walla et al 2002;Miyanari et al 2006;Boesveldt et al 2009) and electroencephalography (EEG) (Tateyama et al 1998;Laudien et al 2006Laudien et al , 2008, had been performed to detect objective olfactory brain responses. In these studies, the orbitofrontal cortex, entorhinal cortex, hippocampus, insular cortex, hypothalamus, piriform cortex, amygdala, and anterior cingulate cortex were reported to be activated by olfactory stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…MEG is another complex neuroimaging technique used in olfactory paradigms [3,[70][71][72][73], and offers high temporal and spatial resolution and high data reliability [74,75]. In several studies, MEG has been used to describe the chronological sequence of different stages of processing in different neural substrates in olfactory paradigms [76].…”
Section: Magneto-encephalography and Chemical Perceptionmentioning
confidence: 99%